ANALISIS TEORI RESEPSI TENTANG REPRESENTASI PERPUSTAKAAN PERGURUAN TINGGI PADA VIDEO PERESMIAN GEDUNG PUSAT INFORMASI DAN PERPUSTAKAAN UNIVERSITAS NEGERI PADANG - Ikhsan, Risky Jumatul; Prihatin, Silverius Djuni (Info Bibliotheca: Jurnal Perpustakaan dan Ilmu Informasi, 2024)
The development of technology and digitalization has encouraged various institutions, including university libraries, to utilize digital platforms such as YouTube as promotional tools. This study analyzes the representation of the Universitas Negeri Padang (UNP) library in the promotional video titled "Peresmian Gedung Pusat Informasi dan Perpustakaan Universitas Negeri Padang" (Inauguration of the Information and Library Center Building of Universitas Negeri Padang) uploaded on the UNP TV YouTube channel. Using a qualitative approach, the research applies reception analysis based on Stuart Hall's encoding-decoding theory. The findings indicate that the video represents the library as a place for studying and discussion, a quiet space, with stereotypical depictions of librarians, a collection limited to books, and a sense of suspicion toward library users. The researcher concludes that this representation fails to reflect the functions of a modern library, which should also encompass social spaces, digital collections, and a friendly relationship with users. The researcher adopts a negotiated and oppositional stance on certain elements of the video, particularly regarding the portrayal of librarians, the library atmosphere, and the featured collection. The study concludes that promotional videos for libraries should reflect inclusivity, trust, and modernity to project a positive institutional image and attract more library users.